La lussazione acuta del gomito - Giannicola, G.; Ascani, C.; Spinello, P. (Lo Scalpello - Journal, 2018)
SIMPLE ACUTE ELBOW DISLOCATION Simple acute elbow dislocation is defined as the loss of bone congruity of the elbow following trauma, without associated bone injuries. An adequate fluoroscopic evaluation of the stability after reduction is mandatory to choose either the conservative or the surgical treatment. Persistent joint instability or incongruency beyond 40° of flexion after reduction or recurrence of dislocation represent the main indication for surgery. The identification and classification of the type of ligamentous and musculotendinous lesions is fundamental to select the correct repair technique. Early rehabilitation is mandatory for rapid recovery of elbow function.